2018
DOI: 10.7185/geochemlet.1813
|View full text |Cite
|
Sign up to set email alerts
|

Properties of molten CaCO3 at high pressure

Abstract: doi: 10.7185/geochemlet.1813We report here the structure of molten CaCO 3 studied by in situ X-ray diffraction using a Paris-Edinburgh press up to 8.7 GPa. Variations are observed in the medium range order with shrinkage of the intermolecular contributions, reflecting higher packing efficiency of the carbonate molecules. Density of the melt is obtained from the radial distribution functions, assuming a constant coordination number of 3 for the C-O contribution. Bulk modulus values increase by a factor of 2 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Density values are reported in Figure 7 along with predictions for lower P melt properties (Kang et al, 2015), P-evolution of crystalline siderite, and with the Earth's seismological PREM model (Dziewonski and Anderson, 1981). Density profile below 40 GPa is calculated using K T,0 value of 80.23 GPa (Kang et al, 2015), consistent with that reported for molten calcite (Hudspeth et al, 2018), and density at room P of 2,500 kg•m −3 by assuming a similar density jump upon melting as for other carbonates for which room P density is known. Comparison with PREM model shows that Fe-carbonate melts are buoyant at all depths.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Density values are reported in Figure 7 along with predictions for lower P melt properties (Kang et al, 2015), P-evolution of crystalline siderite, and with the Earth's seismological PREM model (Dziewonski and Anderson, 1981). Density profile below 40 GPa is calculated using K T,0 value of 80.23 GPa (Kang et al, 2015), consistent with that reported for molten calcite (Hudspeth et al, 2018), and density at room P of 2,500 kg•m −3 by assuming a similar density jump upon melting as for other carbonates for which room P density is known. Comparison with PREM model shows that Fe-carbonate melts are buoyant at all depths.…”
Section: Resultssupporting
confidence: 71%
“…The melting curves of CaCO 3 , Na 2 CO 3 , and FeCO 3 have been measured over most of the upper mantle regime (Kang et al, 2015;Li et al, 2017), and viscosity measurements up to 6 GPa span several compositions [K 2 Ca(CO 3 ) 2 and K 2 Mg(CO 3 ) 2 by (Dobson et al, 1996), CaCO 3 and natural dolomite by (Kono et al, 2014), Na 2 CO 3 by (Stagno, 2018)]. Structural data instead have only been collected on molten CaCO 3 below 10 GPa (Hudspeth et al, 2018) while theoretical investigations of the properties of carbonate melts cover a larger P-range but are also limited to the carbon 3-fold stability field (Vuilleumier et al, 2014;Zhang and Liu , 2015;Du et al, 2018;Desmaele et al, 2019). One main question is therefore how this 3 to 4-fold transition translates in the molten state, and what are the consequences on the physical and chemical properties of carbonate melts?…”
Section: Introductionmentioning
confidence: 99%
“…, at conditions of 1773 and 2073 K. Results are compared with those provided by molecular dynamics (MD) calculations implemented by empirical pair potential force field, and those evaluated by first-principle molecular dynamics (FPMD) proposed by Vuilleumier et al (2014) fitted with Birch-Murnaghan equation of state and those obtained with the radial distribution functions by Hudspeth et al (2018). The EoS retrieved from our study results in a compressibility for the CaCO 3 -liquid intermediate between those proposed byVuilleumier et al (2014) andHudspeth et al (2018) (Fig. 5).…”
supporting
confidence: 71%
“…Results are compared with experimental data from IW75 (Irving and Wyllie, 1975), Li17 (Li et al, 2017) with "Pt sphere" (falling sphere) and ECM (electrical conductivity measurements) experiments, B03 (Buob, 2003), S14 (Shatskiy et al, 2014), and S01 (Suito et al, 2001). (Vuilleumier et al, 2014) and the red/green dots with pressure and density error bars are obtained with the radial distribution functions by Hudspeth et al, (2018).…”
Section: Implications For the Geochemical Signature Of Anorogenic Magmasmentioning
confidence: 99%
“…In contrast, we noted that lateral shift occurs mainly when the starting material begins melting as a consequence of the softening of the powder surrounding the Pt sphere at its initial position. Some experiments performed at P < 2 GPa showed the appearance of bubbles due to CO 2 Kono et al, 2014a;de Grouchy et al, 2017;Hudspeth et al, 2018).…”
Section: Resultsmentioning
confidence: 99%